Inorganic Chemistry 2011
DOI: 10.1201/b12873-3
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Polyphosphate Modulates TRPM8 Channels

Abstract: Background: The complexity of the problem of the origin of life has spawned a large number of possible evolutionary scenarios. Their number, however, can be dramatically reduced by the simultaneous consideration of various bioenergetic, physical, and geological constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(33 citation statements)
references
References 274 publications
1
32
0
Order By: Relevance
“…However, while inorganic photosynthesis could provide primordial organisms with food, those organisms were unlikely to utilize the electron vacancies generated within mineral crystals. In case of sulfides, the light‐generated vacancies are promptly refilled by sulfide anions yielding elemental sulfur (see Schoonen et al , Mulkidjanian , Mulkidjanian and Galperin , and references therein).…”
Section: Resultsmentioning
confidence: 99%
“…However, while inorganic photosynthesis could provide primordial organisms with food, those organisms were unlikely to utilize the electron vacancies generated within mineral crystals. In case of sulfides, the light‐generated vacancies are promptly refilled by sulfide anions yielding elemental sulfur (see Schoonen et al , Mulkidjanian , Mulkidjanian and Galperin , and references therein).…”
Section: Resultsmentioning
confidence: 99%
“…These networks are proposed to have served as the Earth's first biotopes (see the text and the accompanying article [97]). The picture uses data from refs.…”
Section: Discussionmentioning
confidence: 99%
“…slowly (Mulkidjanian 2009). On the other hand, Zn can be stripped and remobilized from buried chimney fragments, and concentrated at the seawater interface due to some waterrelated geological activities (Edmond et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…1979), it has been found that sphalerite (ZnS) and other metal sulphide minerals widespreadly occurred therein. Among these sulphide species, ZnS precipitates occurred more slowly (Mulkidjanian 2009). On the other hand, Zn can be stripped and remobilized from buried chimney fragments, and concentrated at the seawater interface due to some water-related geological activities (Edmond et al .…”
Section: Discussionmentioning
confidence: 99%